2010
DOI: 10.1111/j.1530-0277.2010.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Alcohol Intake, Reduced Flexibility of Alcohol Drinking, and Evidence of Signs of Alcohol Intoxication in Sardinian Alcohol‐Preferring Rats Exposed to Intermittent Access to 20% Alcohol

Abstract: These data suggest that the "Wise" procedure is effective in inducing marked increases in alcohol intake in sP rats. These increases are associated with a reduced flexibility of alcohol drinking (suggesting the development of "behavioral" dependence) and produce signs of alcohol intoxication that are not detected when sP rats are exposed to the more conventional CA10% condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 36 publications
10
37
0
Order By: Relevance
“…We interpret this to indicate that IAA rats may already be at maximum in terms of expression of pathological drinking. Finally, a study in an alcohol-preferring rat strain for less • than 1 month found relative resistance to quinine adulteration in IAA versus CAA in rats, but still some sensitivity to quinine in the former (Loi et al 2010). This fi nding agrees with our study showing some quinine sensitivity at ~1½ months relative to 3-4 months of IAA intake; we used outbred Wistar rats (Hopf et al 2010), which consume alcohol but are not selected to be alcoholpreferring.…”
Section: Aversion Resistance With Intermittent Versus Continuous Accesupporting
confidence: 90%
See 1 more Smart Citation
“…We interpret this to indicate that IAA rats may already be at maximum in terms of expression of pathological drinking. Finally, a study in an alcohol-preferring rat strain for less • than 1 month found relative resistance to quinine adulteration in IAA versus CAA in rats, but still some sensitivity to quinine in the former (Loi et al 2010). This fi nding agrees with our study showing some quinine sensitivity at ~1½ months relative to 3-4 months of IAA intake; we used outbred Wistar rats (Hopf et al 2010), which consume alcohol but are not selected to be alcoholpreferring.…”
Section: Aversion Resistance With Intermittent Versus Continuous Accesupporting
confidence: 90%
“…Cocaine intake despite pairing with footshock is considered the most robust model for compulsive addiction (Deroche-Gamonet et al 2004;Vanderschuren and Everitt 2004), but to our knowledge similar experiments have not been reported with alcohol. Instead, a number of studies in rodents, using bitter-tasting quinine to examine aversionresistant alcohol intake, have reported that the animals tolerate in alcohol the same concentrations of quinine that dramatically reduce water intake (Hopf et al 2010;Loi et al 2010;Spanagel et al 1996;Spanagel and Holter 1999;TuryabahikaThyen and Wolffgramm 2006;Vengeliene et al 2009;Wolffgramm and Heyne 1991;Wolffgramm et al 2000).…”
Section: Rodent Models Of Aversion Resistancementioning
confidence: 97%
“…In that study, rats that received intermittent access to alcohol (i.e., every other day) showed a gradual increase in alcohol intake over time. This escalation of alcohol intake over time in intermittent/every-other-day models has been confirmed by recent studies that have reintroduced this approach in the field of alcoholism research (Simms et al, 2008;Loi et al, 2010;Hwa et al, 2011;Melendez, 2011;Gilpin et al, 2012). Likewise, classic studies by Wolffgramm (1991), Wolffgramm andHeyne (1991, 1995) demonstrated that rats increase their levels of alcohol intake after lengthy periods (i.e., months) of relatively stable ethanol intake.…”
Section: Escalation Of Drug Usementioning
confidence: 52%
“…They are reported to achieve pharmacologically relevant BEC at each drinking session and to exhibit "binge"-like drinking behavior (i.e., three drinking bouts per day; Loi et al 2010).…”
Section: Models Of Alcohol Consumptionmentioning
confidence: 99%